Voters’ Attributions of Psychopathic Traits to Donald Trump and Hillary Clinton After the 2016 U.S. Presidential Election and the 2020 Trump Impeachment Trial - Paul E. Jose; Ira J. Roseman; Anna Geiserman; Taylor Winter; Boris Bizumic (Europe's Journal of Psychology, 2025)
We sought to determine if voters’ personological characteristics influence perceptions of psychopathic traits in political candidates and predict vote choice. Our first dataset was collected soon after the 2016 U.S. presidential election between Hillary Clinton and Donald Trump. The sample, 159 Trump voters and 154 Clinton voters, rated their own authoritarian beliefs and their perceptions of psychopathic tendencies in both candidates, and reported their vote. As predicted, Clinton voters perceived low levels of psychopathic tendencies in Clinton and high levels of psychopathic tendencies in Trump, and Trump voters displayed the opposite pattern. A concurrent mediation analysis found that highly authoritarian voters perceived Trump to be low on psychopathic tendencies, and they tended to vote for Trump. These results were replicated from a different sample of 300 voters about three years later, soon after Trump’s first impeachment. The results suggest that authoritarian beliefs profoundly color perceptions of psychopathy in political candidates.